DEVELOPMENT OF GIFTED PERSONALITY IN THE CONTEXT OF CULTURAL-HISTORICAL PSYCHOLOGY OF L. S. VYGOTSKY - Muzуka, Olena; Romanenko, Kateryna (Educological discourse, 2022)
The article presents the results of the analysis of the scientific views of L. S. Vygotsky on giftedness and abilities in the context of the theory of cultural-historical development. Giftedness is considered by the scientist as a universal prerequisite for all people for their personal development in specific cultural-historical conditions. Special giftedness (intellectual, motor, practical, emotional, musical, etc.) is the result of the purposeful development of the abilities and structures of the personality in their interconnection and mutual influence. Thus, the development of a gifted personality as a whole is a process of mastering historically established forms of activity and relationships. The main mechanism for the development of a gifted person in the educational process is the solution of the dynamic contradiction between the level of actual development and the zone of proximal development. The ideas of L. S. Vygotsky about an integral gifted personality and the directions of its development are consonant with the goals facing modern education, and are applied in the theory and practice of building a personality-oriented New Ukrainian School.